Comparative evaluation of intramedullary interlocking nailing and end-threaded pinning (positive profile) for fixation of femoral fractures in dogs - KUMAR, HARISH; TYAGI, S P; KUMAR, AMIT; KUMAR, ADARSH; SINGH, SUKHPREET (The Indian Journal of Animal Sciences, 2020)
The study included 14 cases of femur fracture in which two different techniques namely intramedullary interlocking nailing (IILN) (group-I; 9 cases) and end threaded pinning (ETP) (group-II; 5 cases) were used for fixation of the fracture. The mean duration of surgical procedure was higher in group I as compared to group II. The extent of manipulation/soft tissue damage was slightly more in group I than in group II. The technique of IILN was relatively more difficult than ETP. The extent of fracture reduction and fixation was relatively better in group I than in group II. The weight-bearing improved gradually in both the groups but found to be better in group I than group II. The functional outcome of the fractured limb was superior in fracture fixed by IILN as compared to other group.